KONSEKUENSI HUKUM KELALAIAN PEMBAYARAN PESANGON OLEH PENGUSAHA PASCA PENGESAHAN UU CIPTA KERJA - Jeniffer Angelia Ong; Febri Jaya; Ampuan Situmeang (HUKMY : Jurnal Hukum, 2025)
Following the enactment of the Job Creation Law, significant changes have occurred in Indonesia’s labour law framework, particularly regarding severance pay rights previously regulated under the Labor Law. This study aims to analyse the concrete changes in legal norms concerning employers’ obligations to pay severance and to assess the legal consequences of neglecting these obligations after employment termination. Using a normative juridical approach with comparative and conceptual analysis methods, the findings reveal that the Job Creation Law grants greater flexibility to employers in terminating employment and reduces the compensation owed to workers. These changes increase the risk of employers neglecting severance payments and create legal uncertainty, especially due to weak enforcement of administrative and civil sanctions. Therefore, a policy evaluation in labour law is necessary to ensure the protection of workers’ rights in a firmer, fairer, and non-discriminatory manner.